2018
DOI: 10.1021/acs.est.8b03659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transient Wave Forcing on the Behavior of Arsenic in a Nearshore Aquifer

Abstract: Groundwater–coastal water interactions influence the fate of inorganic chemicals in nearshore aquifers and their flux to receiving coastal waters. This study evaluates the impact of variable wave conditions on the geochemical changes and distribution of mobile arsenic (As) in a nearshore aquifer. Field measurements in a sandy nearshore aquifer on Lake Erie, Canada, are presented with geochemical changes analyzed over a period of high waves. A numerical model of wave-induced groundwater flow dynamics, validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…For example, Xin et al (2010) developed a phase‐averaged approach where wave effects were represented by a wave‐induced onshore hydraulic gradient above the mean sea level, referred to as wave setup. This approach has been used in numerous wave relevant studies (Anwar et al, 2014; Malott et al, 2017; Rakhimbekova et al, 2018; Robinson et al, 2014). Geng and Boufadel (2015) developed a “net inflow” approach to upscale wave effects on subsurface flow and transport processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Xin et al (2010) developed a phase‐averaged approach where wave effects were represented by a wave‐induced onshore hydraulic gradient above the mean sea level, referred to as wave setup. This approach has been used in numerous wave relevant studies (Anwar et al, 2014; Malott et al, 2017; Rakhimbekova et al, 2018; Robinson et al, 2014). Geng and Boufadel (2015) developed a “net inflow” approach to upscale wave effects on subsurface flow and transport processes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that complex groundwater mixing occurs in the swash zone due to high‐frequency inundation and seawater infiltration by individual waves (Cartwright et al, 2002; Geng et al, 2014, 2017; Geng & Boufadel, 2015; Heiss et al, 2014; Malott et al, 2017; Xin et al, 2010). Swash and tidal action are a primary control on nearshore biogeochemical processes and submarine discharge of various chemical species (e.g., nutrients, carbon, arsenic, and trace elements) into coastal waters (Boehm et al, 2006; Brown & Boehm, 2016; Kim et al, 2017; Lässig, 2019; Mohapatra et al, 2011; Praveena et al, 2012; Rakhimbekova et al, 2018; Waska, 2019). Kim et al (2020) revealed that intertidal groundwater‐seawater mixing driven by tides likely creates a dynamic reactive circulation cell, where areas with high denitrification rates shift landward and seaward along the mixing zone though spring‐neap cycles.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, hot moments in STE can be created through movements of the salinity gradient, when, e.g., phosphorus can desorb from aquifer sediment with increasing salinity and cause a spike of P fluxes to the ocean that is not directly connected to terrestrial or marine inputs (Flower et al, 2017). Hot moments can also result from shifts in groundwater flow paths due to changed wave activity, which have been hypothesized to trigger pulses of arsenic transport into coastal waters due to instability of iron oxyhydroxides under changing redox conditions (Rakhimbekova et al, 2018). Water residence time is an essential factor influencing chemical reaction kinetics in the STE.…”
Section: Biogeochemical Cycling In Subterranean Estuariesmentioning
confidence: 99%
“…To address lake water quality impairment, there is increasing need to identify, quantify, and manage all the sources and pathways delivering pollutants to lakes. While often overlooked, groundwater discharge can be an important delivery pathway for lakes (Knights et al, 2017; Lewandowski et al, 2015; Meinikmann et al, 2015; Rakhimbekova et al, 2018; Rakhimbekova et al, 2021; Rosenberry et al, 1999). Groundwater can enter a lake either directly from an aquifer, termed lacustrine groundwater discharge (LGD), or indirectly through groundwater‐fed streams that flow into the lake (termed indirect groundwater discharge) (Grannemann et al, 2000).…”
Section: Introductionmentioning
confidence: 99%